ACTION ON SMOOTH MUSCLES OF CARDIAC GLUCOSIDES AND REAGENTS INHIBITING SULFHYDRYL ENZYMES - ALANIS, JESUS R (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
Evidence is presented in favor of the theory previously stated, that the U wave is caused by repolarization of the septum which is slowed because of bilateral intraventricular pressure
ARCH INST CARDIOL MEX
Keywords: ACTION, SMOOTH, MUSCLES, CARDIAC, GLUCOSIDES, REAGENTS, INHIBITING, SULFHYDRYL, ENZYMES; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA